Efforts To Improve Language And Writing Skills In Students Through Listening To News - Theresia Materna Br Sagala; Debora Jesika Sihotang; Maharani Yasika; Nabilah Najwa Ghassani; Putri Rohni R Sitio; Mansyur Tarigan (FKIP, Universitas Palangka Raya, 2023)
The purpose of this study is to explore the efforts to enhance language and writing skills in students by utilizing news listening. This research follows a qualitative approach with a Literature Review method and focuses on students majoring in English education. The study results indicate that the endeavor to improve the language and writing abilities of students through news listening has a positive impact on enhancing their communication and writing skills. Additionally, this activity contributes to shaping critical and analytical thinking in response to the information they receive, structuring ideas, and detailed composition in their written work.